Islam and Body Discipline: Remove Tattoos and Da'wah Paths of Hijrah Care Community - Sipa, Amar Muhyi Diinis; Lubis, Nikmah (Jurnal Dakwah Risalah, 2023)
This article examines the hijrah movement within the Hijrah Care Community through the medium of the Free Tattoo Removal Movement. The emergence of Hijrah Care and the Free Tattoo Removal Movement stems from the street culture da'wah and focuses on street children who want to undergo hijrah but still have tattoos on their bodies. Therefore, Hijrah Care endeavors to provide a path of repentance for street children by organizing the Free Tattoo Removal Program. Data were obtained through interviews and observations of Hijrah Care's social media accounts. This article demonstrates that the Free Tattoo Removal Movement serves as a means of da'wah for the Hijrah Care Community to construct an ideological discourse through religious studies, which participants of the tattoo removal must adhere to. There has been a fundamental change in perception and meaning regarding tattoos. Before hijrah, tattoos were seen as art and a representation of themselves and their group. However, post-hijrah, their perception and understanding of tattoos have changed drastically. Tattoos are no longer perceived as art but are now viewed with negative sentiment and even despised.